ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PERMINTAAN TENAGA LISTRIK KONSUMEN SEKTOR KONSUMTIF PERUSAHAAN LISTRIK NEGARA - Aminullah Assagaf (EKUITAS (Jurnal Ekonomi dan Keuangan), 2010)
This research aims to analyse electricity demand, and focus for consumptive sector in PT Perusahaan listrik Negara (Persero) or PT PLN (Persero). While selected by consumptive sector is some region in Jawa Bali and otuside Jawa Bali. Step of research and process result based on SPSS calculation, and use time series data year 1995 - 2009. As for used analysis model follow its data distribution that is the non linear regression model being based on Ln with dependent variable is demand electricity or kWh sales, and independent variable consist of install capacity, average tariff, and rate of capacity using percustomers. Obtain result that install capacity and rate of capacity using percustomers have given positif impact, and average tariff have given negative impact. All of that independent variable have significant influence, and install capacity variable most its influence significant to electricity demand of consumptive sector. PLN’s management has to observe growth of explanatory variable to make policy for demand and supply equilibrium and toward customers satisfaction.